Optimal Regeneration Regime under Continuous Crown Cover Requirements in Cork Oak Woodlands - Almeida Ribeiro, Nuno (2013)
In the present work the cork oak tree spatial growth simulator CORKFITS is used to create candidate scenarios for generating a large set of regeneration regimes combining both time and intensity factors with the individual tree spatial information. An optimal regeneration regime under continuous crown cover requirements is sought by applying a dynamic programming algorithm. It is shown that the crown cover constraint influences the total cork production potential in a negative way. The target cover constraint of 50% decreases the cork production by 66% from the potential in 40 years in our mature plot, and approximately 43% in our young plot. Higher crown cover constraint of 70% decreases the potential cork production approximately by 54% in the mature plot and does not have any influence on the younger plot. The observed losses in cork production in relation with the potential with the crown cover constrains need to be compensated economically by the higher availability of growing space for the grazing and livestock part of the montado/dehesa production system.